Avaliação nutricional da torta de dendê para suplementação de ruminantes na Amazônia Oriental - COSTA, Dayana Alves da (Universidade Federal do Pará, 2014)
The study was carried out at the Eastern Amazon Research Center of Embrapa, in Belem, Para State, Brazil (1º28'S 48º27'W of Greenwich), with the objective of evaluate the influence of the addition of the palm kernel cake (Elaeis guineensis) as alternative feed supplementation of ruminants, in the critical periods of forage production of in the Amazon Eastern. The nutritional characteristics of palm kernel cake was determined during twenty one days, using sixteen sheep, in individual metabolic cage, distributed in a completely randomized experimental design, with four treatments and four replications. The experimental rations (T1, T2, T3 and T4) contained Brachiaria humidicola and palm kernel cake, at four levels (10%, 20%, 30% and 40%). The consumption of dry matter (g/day) and % of live weight were 666.6 and 2.5; 686.9 and 2.4; 649.4 and 2.4; e 540.9 and 2.0, of organic matter 706.5; 710.8; 708.1 and 632.3 g/day, and of crude protein 37.3; 42.9; 58.7 and 56.4 g/day. The fiber in neutral detergent consumption in g/day, were 584.7; 583.5; 565.2 and 527.0. The coefficients of digestibility were 50.3; 47.8; 52.3; and 55.2%, in dry matter basis, and 50.8; 49.6; 53.5; and 56.3%, in organic matter basis, and the crude protein contents were 48.0; 38.7; 66.8; 69.4%, in T1, T2, T3 and T4, respectively. The palm kernel cake shows good feeding potential, with high dry matter and good nutritional value, being considered as an alternative for feeding supplementation for ruminants, mainly at the level of 30%, and allows greater consumption and digestibility of dry matter, organic matter, crude protein, with adequate supplement of energy.